To apply the properties of operations to simplify the expression 5(k - 4) + k(6 + 3), we first distribute the 5 and k to the terms inside the parentheses:
5(k - 4) + k(6 + 3)
= 5k - 20 + 6k + 3k
Next, we combine like terms:
= 5k + 6k + 3k - 20
= 14k - 20
Thus, the correct answer is 14k - 20.
Apply the properties of operation to 5(k - 4) + k(6 + 3) to generate an equivalent and fully simplified expressions.
11k - 17
14k - 17
14k - 20
11k - 1
3 answers
That is wrong
Apologies for the incorrect response. Let's go through the simplification process again:
5(k - 4) + k(6 + 3)
= 5k - 20 + 6k + 3k
= (5k + 6k + 3k) - 20
= 14k - 20
So, the correct answer is 14k - 20.
5(k - 4) + k(6 + 3)
= 5k - 20 + 6k + 3k
= (5k + 6k + 3k) - 20
= 14k - 20
So, the correct answer is 14k - 20.